2022
DOI: 10.1093/mnras/stac3436
|View full text |Cite
|
Sign up to set email alerts
|

Energy wrinkles and phase-space folds of the last major merger

Abstract: Relying on the dramatic increase in the number of stars with full 6D phase-space information provided by the Gaia Data Release 3, we resolve the distribution of the stellar halo around the Sun to uncover signatures of incomplete phase-mixing. We show that for the stars likely belonging to the last massive merger, the (vr, r) distribution contains a series of long and thin chevron-like overdensities. These phase-space sub-structures have been predicted to emerge following the dissolution of a satellite, when it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 87 publications
(99 reference statements)
2
18
0
Order By: Relevance
“…M31 is remarkably similar to the Milky Way in that the inner halos of both galaxies are dominated by stars from a single accretion event. Indeed, a recent study of the kinematics of Milky Way stars near the Sun reports chevron-shaped kinematic substructures (Belokurov et al 2023) that are reminiscent of those reported here. If the progenitor of the M31 shell system studied here is 10 10 M e , M31 may provide a close analog to what our own galaxy looked like several gigayears ago.…”
supporting
confidence: 76%
“…M31 is remarkably similar to the Milky Way in that the inner halos of both galaxies are dominated by stars from a single accretion event. Indeed, a recent study of the kinematics of Milky Way stars near the Sun reports chevron-shaped kinematic substructures (Belokurov et al 2023) that are reminiscent of those reported here. If the progenitor of the M31 shell system studied here is 10 10 M e , M31 may provide a close analog to what our own galaxy looked like several gigayears ago.…”
supporting
confidence: 76%
“…However, for relatively recent mergers, there will not be sufficient time for virialization, resulting in plenty of substructures both in the stellar and in the DM component [85][86][87][88][89][90][91][92][93][94][95][96][97]. The presence of such additional stellar substructures (beyond the MW stars) have been detected by different sky-surveys like Gaia [83,90,[97][98][99][100], SDSS [90], LAMOST [101,102], etc., and have also been predicted in various N-body simulations [103][104][105][106][107][108][109][110][111].…”
Section: Jhep02(2023)200mentioning
confidence: 55%
“…The spectra are provided for ∼ 220 million stars in Gaia with 𝐺 < 17.65. Despite their low resolution, several studies have demonstrated that the information content is sufficient to measure bulk spectroscopic parameters (𝑇 eff , log 𝑔, [M/H], Liu et al 2012;Witten et al 2022;Xylakis-Dornbusch et al 2022;Andrae et al 2022;Fouesneau et al 2022;Creevey et al 2022;Belokurov et al 2022;Rix et al 2022) although detailed chemical abundances are likely too challenging (Gavel et al 2021). However, particularly in cooler stars, the presence of molecular features in these spectra is detectable (Lucey et al 2022) enabling more accurate metallicity determinations and detailed carbon abundances.…”
Section: Unsupervised Classification Of O-rich/c-rich Long-period Var...mentioning
confidence: 99%